# Solve:12x - 6x - 13 = 0

The solution to this question is obtained by combining the like terms, thereby simplifying the given expression.

## Answer: The value of x for the given equation 12x - 6x - 13 = 0 is 13/6.

Let's find the value of x

**Explanation:**

12x - 6x -13 = 0

12x - 6x = 13 --------> (shifting -13 from LHS to RHS)

6x = 13 --------------> (12x and 6x are like terms)

x = 13 / 6

### Thus, the solution of the given equation 12x - 6x - 13 = 0 is 13/6.

Math worksheets and

visual curriculum

visual curriculum